2017
DOI: 10.1080/00131911.2017.1316239
|View full text |Cite
|
Sign up to set email alerts
|

Civic participation of high school students: the effect of civic learning in school

Abstract: Building active and informed citizens is a major part of civics and citizenship education in order to enhance and sustain democracies. Civic learning and civic action opportunities within school contexts are commonly claimed to promote an active and informed citizenry. In the present research, we examine the meaning of formal civics education and the role of students' participation in a range of curricular and extracurricular activities. Multilevel analyses yield quite stable results across two cohorts of Aust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 43 publications
0
33
0
6
Order By: Relevance
“…Several studies of citizenship education reviewed in this study have reported on quantitative data. For example, existing instruments measure the impact of citizenship education on young people's civic and political engagement (e.g., Hoskins et al, 2012;Kahne & Sporte, 2008;Keating & Janmaat, 2015;Lin, 2015;Reichert & Print, 2017), and the ICCS instrument covers a range of activities in school, such as students' participation in school democracy and the measure of an open classroom climate (Huang et al, 2017;Schulz et al, 2017). The instrument I designed in this study represents a methodological contribution to developing quantitative research on social studies instruction.…”
Section: Methodological Contributionsmentioning
confidence: 99%
“…Several studies of citizenship education reviewed in this study have reported on quantitative data. For example, existing instruments measure the impact of citizenship education on young people's civic and political engagement (e.g., Hoskins et al, 2012;Kahne & Sporte, 2008;Keating & Janmaat, 2015;Lin, 2015;Reichert & Print, 2017), and the ICCS instrument covers a range of activities in school, such as students' participation in school democracy and the measure of an open classroom climate (Huang et al, 2017;Schulz et al, 2017). The instrument I designed in this study represents a methodological contribution to developing quantitative research on social studies instruction.…”
Section: Methodological Contributionsmentioning
confidence: 99%
“…Moreover, Ekman and Zetterberg (2010) claim that political socialisation is increasingly taking place in the family and outside of school. A study in Australia also showed that participation in the local community and social policy activities increased students' intentions for future political participation more than being taught civic issues at school (Reichert and Print 2018).…”
Section: Previous Research On Social Policy Participation and Involvementioning
confidence: 99%
“…Low youth civic participation, particularly in university students, is a situation that captivates not only the actors involved in promoting greater voter turnout, but is a cause for concern from researchers in the areas of social sciences (Reichert;Print, 2018). In view of this worrying removal of students, it is emphasized the need to know the situation of institutions and autonomy in student organizations, especially their importance in exercising rights and duties in order to increase the levels of university political participation without ideological impositions.…”
Section: Values Of University Students Portugal/brazilmentioning
confidence: 99%